2017
DOI: 10.1038/ncomms15736
|View full text |Cite
|
Sign up to set email alerts
|

Water pumping in mantle shear zones

Abstract: Water plays an important role in geological processes. Providing constraints on what may influence the distribution of aqueous fluids is thus crucial to understanding how water impacts Earth's geodynamics. Here we demonstrate that ductile flow exerts a dynamic control on water-rich fluid circulation in mantle shear zones. Based on amphibole distribution and using dislocation slip-systems as a proxy for syn-tectonic water content in olivine, we highlight fluid accumulation around fine-grained layers dominated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 67 publications
5
52
0
Order By: Relevance
“…This is also confirmed by chemical data that show strong enrichments of fine-grained minerals in (proto)mylonites in fluid mobile elements (especially boron; Prigent et al, 2018). This observation is also in agreement with the predominant activation of olivine (001)[100] dislocation slip systems in (proto)mylonites to ultramylonite/UMB (Figure 7), which is generally activated in hydrous conditions (Cao et al, 2015;Harigane et al, 2013;Hidas et al, 2016;Jung et al, 2014;Katayama et al, 2004;Mehl et al, 2003;Michibayashi & Oohara, 2013;Précigout et al, 2017). The geochemistry of newly crystallized fine grains and whole rock isotopic compositions indicate that these aqueous fluids bear a subduction signature (Khedr et al, 2014;Prigent et al, 2018;Yoshikawa et al, 2015).…”
Section: Fluid-assisted Deformation and Fluid Focusing In Shear Zonessupporting
confidence: 84%
See 1 more Smart Citation
“…This is also confirmed by chemical data that show strong enrichments of fine-grained minerals in (proto)mylonites in fluid mobile elements (especially boron; Prigent et al, 2018). This observation is also in agreement with the predominant activation of olivine (001)[100] dislocation slip systems in (proto)mylonites to ultramylonite/UMB (Figure 7), which is generally activated in hydrous conditions (Cao et al, 2015;Harigane et al, 2013;Hidas et al, 2016;Jung et al, 2014;Katayama et al, 2004;Mehl et al, 2003;Michibayashi & Oohara, 2013;Précigout et al, 2017). The geochemistry of newly crystallized fine grains and whole rock isotopic compositions indicate that these aqueous fluids bear a subduction signature (Khedr et al, 2014;Prigent et al, 2018;Yoshikawa et al, 2015).…”
Section: Fluid-assisted Deformation and Fluid Focusing In Shear Zonessupporting
confidence: 84%
“…Different mechanisms have been invoked to account for these combined processes of grain size reduction and phase mixing in ductile mantle shear zones: dislocation-mediated dynamic recrystallization and GBS-related grain switching events (e.g., Linckens et al, 2014), dynamic recrystallization and stress-induced differential cation diffusion (Tasaka et al, 2017), or dispersed nucleation of fine grains through dissolutionprecipitation processes (Hidas et al, 2016;Précigout et al, 2017;Précigout & Stünitz, 2016), associated with metamorphic reactions (De Ronde & Stünitz, 2007;De Ronde et al, 2005;Newman et al, 1999;Toy et al, 2010;Vissers et al, 1995) or melt-rock interaction (Dijkstra et al, 2002;Kaczmarek & Tommasi, 2011). The evidence for dislocation mobility in olivine and pyroxene (undulose extinctions and subgrain walls; Figures 3 and 4) and the occurrence of olivine triple junctions suggest that dynamic recrystallization by subgrain rotation partly contributed to reducing grain size.…”
Section: Mechanism (S) Of Grain Size Reduction and Phase Mixingmentioning
confidence: 99%
“…Both of these thermometers are based on the closure temperatures of major element diffusion in their host mineral(s). As observed in other studies that have applied multiple thermometers (e.g., Birner et al, 2017;Dygert & Liang, 2015;Hidas et al, 2013;Précigout et al, 2017), the temperatures recorded by each thermometer vary systematically, reflecting differences in closure temperature of the different mineral systems as the peridotite cooled.…”
Section: Geothermometrysupporting
confidence: 57%
“…To date, geological research has identified evidence for creep cavitation in natural ultramylonites from the middle crust (Behrmann and Mainprice, 1987;Mancktelow et al, 1998;Herwegh and Jenni, 2001;Fusseis et al, 2009;Kilian et al, 2011;Rogowitz et al, 2016), the lower crust (Zá-vada et al, 2007;Menegon et al, 2015) and in mantle rocks (Rovetta et al, 1986;Précigout et al, 2017). Experimental work has shown that octachloropropane, quartzite, diabase, feldspar aggregates, anorthite-diopside aggregates, olivineclinopyroxene aggregates and calcite-muscovite aggregates can develop creep cavities (Caristan, 1982;Hirth and Tullis, 1989;Ree, 1994;Dimanov et al, 2007;Rybacki et al, 2008;Delle Piane et al, 2009;Précigout and Stünitz, 2016).…”
Section: Introductionmentioning
confidence: 99%